2019
DOI: 10.3390/ijms20225560
|View full text |Cite
|
Sign up to set email alerts
|

Water Extract of Cryphaea heteromalla (Hedw.) D. Mohr Bryophyte as a Natural Powerful Source of Biologically Active Compounds

Abstract: Bryophytes comprise of the mosses, liverworts, and hornworts. Cryphaea heteromalla, (Hedw.) D. Mohr, is a non-vascular lower plant belonging to mosses group. To the date, the most chemically characterized species belong to the liverworts, while only 3.2% and 8.8% of the species belonging to the mosses and hornworts, respectively, have been investigated. In this work, we present Folin–Ciocalteu and oxygen radical absorbance capacity (ORAC) data related to crude extracts of C. heteromalla obtained by three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 61 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…The most abundant group within the berry extracts was flavan-3-ols, including flavonoid oligomers such as procyanidin dimer and procyanidin trimer. Reports published so far by other groups showed that purified procyanidins inhibited cell viability and/or induced cell apoptosis of breast cancer cells (MCF-7 and MDA-MB-468 lines), lung cancer (A427 lines), prostate cancer (DU145 line), colorectal cancer (HCT-8, HT29, and Caco-2 lines) and bladder cancer (BIU87 lines) without a cytotoxic effect on untransformed counterparts [ 51 ]. It was also shown that the chemical structure of polyphenols was a decisive factor in their anti-cancer effectiveness, and, in the case of oligomeric flavan-3-ols, their degree of polymerization positively correlated with the reduced viability of neoplastic cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most abundant group within the berry extracts was flavan-3-ols, including flavonoid oligomers such as procyanidin dimer and procyanidin trimer. Reports published so far by other groups showed that purified procyanidins inhibited cell viability and/or induced cell apoptosis of breast cancer cells (MCF-7 and MDA-MB-468 lines), lung cancer (A427 lines), prostate cancer (DU145 line), colorectal cancer (HCT-8, HT29, and Caco-2 lines) and bladder cancer (BIU87 lines) without a cytotoxic effect on untransformed counterparts [ 51 ]. It was also shown that the chemical structure of polyphenols was a decisive factor in their anti-cancer effectiveness, and, in the case of oligomeric flavan-3-ols, their degree of polymerization positively correlated with the reduced viability of neoplastic cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that combination therapy is known to be more effective in treating cancers as it reduces the chances of developing drug resistance. It was shown, among others, that polyphenolic compounds apart from the mentioned mutual combinations could also be combined with other natural compounds such as sugar derivatives, glycosides, peptides, and amino acids [ 51 ]. These studies seemed to be highly relevant in the context of our recent report showing that plant-derived amino acid canavanine (an arginine analog) had a strong cytotoxic effect on two human glioblastoma cell lines, U87MG and U251MG [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, 4-O-caffeoylquinic, 5-O-caffeoylquinic and caffeic acids were detected in the two mosses Brachytheciastrum velutinum and Kindbergia praelonga [ 77 ]. Besides these compounds, bryophytes are known to produce derivatives of benzoic acids [ 42 , 84 ], stilbenes [ 85 ], coumarins [ 86 , 87 ] and different flavonoids, including flavones (apigenin and luteolin derivatives for example) [ 77 ]; flavonols (quercetin) [ 77 ], isoflavones [ 88 ], dihydroflavonols [ 89 ] and aurones [ 90 , 91 ]. Interestingly, genes involved in phenylpropanoid-polyamine biosynthesis are not found in bryophytes [ 92 ].…”
Section: Phytochemistry Of Bryophyte’s Antifungal Metabolitesmentioning
confidence: 99%
“…Authors compared Sphagnum’s metabolite signature to the metabolite composition of different plant species with known antimicrobial effects (i.e., medicinal plants), finding 17 putative antimicrobial substances: network analysis identified 211 known compounds and 21 unknown compounds that were first neighbors of these 17 antimicrobial compounds, suggesting there are potentially other compounds in the Sphagnum metabolome with antimicrobial properties. Other compounds known for their potential against fungi as phenolic compounds, benzoic, caffeic and coumaric acids derivatives, have been detected in a study carried out by HPLC-TOF/MS on Cryphaea heteromalla extracts [ 84 ].…”
Section: Mining With the Omic-technologies: New Generation Approacmentioning
confidence: 99%
“…The Folin-Ciocalteu procedure is one of the methods that are most often used to determine the total phenolic compounds concentration. It has been applied to the analysis of phenolic compounds in Cytisusvillosus [50], Cryphaeaheteromalla [51], elderberry [52], rice [53], and açai [10], among others.…”
Section: Introductionmentioning
confidence: 99%